2017
DOI: 10.1016/j.jamcollsurg.2017.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Positivity in Appendiceal Adenocarcinoma: Should Size Matter?

Abstract: In appendiceal adenocarcinoma, the rate of lymph node metastases is substantial, even for small tumors. Tumor size should play no role in the decision of whether to perform a hemicolectomy. Appendectomy alone does not produce an adequate lymph node sample. Right hemicolectomy should be performed for all appendiceal adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…A recent National Cancer Database study found that 19% of AAs larger than 1 cm had lymph node involvement; the rate was 28% for AAs that were 1 to 2 cm. 66 Rates of lymph node involvement were 0%, 11%, and 12% for tumors that were in situ, T1, and T2, respectively. These numbers were quite similar to those for primary colon adenocarcinomas.…”
Section: Managementmentioning
confidence: 92%
“…A recent National Cancer Database study found that 19% of AAs larger than 1 cm had lymph node involvement; the rate was 28% for AAs that were 1 to 2 cm. 66 Rates of lymph node involvement were 0%, 11%, and 12% for tumors that were in situ, T1, and T2, respectively. These numbers were quite similar to those for primary colon adenocarcinomas.…”
Section: Managementmentioning
confidence: 92%
“…Our data show that the lymph node metastasis in right colon cancer patients first appear in the bowel axis lymph nodes, and then to the central lymph nodes. Colon tumor cells tend to metastasize to lymph nodes close to the axis of the bowel [ 28 , 29 ]. In addition, the total metastasis rate of right colon cancer in T1, T2, T3, and T4 were 11.1%, 14.3%, 42.2%, and 69.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the number of lymph nodes examined was not associated with LN+ in this study ( P = .207). Based on the information provided in the NCDB for appendiceal adenocarcinomas, it seems that the nationwide management of MAC varies and may not be representative of recommendations for lymph node harvest or formal hemicolectomy 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, LN+ appears to confer a worse prognosis even in the setting of peritoneal disease in patients undergoing cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) 9‐11 . Because of the relatively high frequency of regional LN+ in patients with any appendiceal adenocarcinoma and the prognostic value of LN+ in this population, the general consensus is to perform a right colectomy, irrespective of the characteristics of the appendiceal cancer, particularly in the presence of high‐grade disease 12,13 . Even so, if providers deem there is a low probability of LN+ in a patient with MAC, they may opt to not offer a hemicolectomy.…”
Section: Introductionmentioning
confidence: 99%